The Effect of Applying the Problem Based Learning Model on Critical Thinking and Problem Solving Skills in Islamic Learning for Students in Pondok pesantren in Jawa Timur - HALIMATUS , SYA'DIYAH (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2023)
The active participation process of students in Islamic boarding schools can support the learning process of Islamic religious education to be more effective and meaningful. This active learning uses the PBL method which is able to improve critical thinking and student learning outcomes. Therefore, teachers need to facilitate students with appropriate learning methods such as learning using the problem based learning method so that students will be actively involved in the learning process, the method used in this research using a pre test post test design, a sample of 30 Islamic boarding school students in Jember, the results of the research show that the problem based learning method is able to improve critical thinking skills and learning outcomes of Pesantren Islamic boarding school students